Impact of Weight-Based Stigma Coping Strategies of Plus-Size Females on Apparel Store Choice: The Moderating Effect of Body Esteem - Ağyel, Müge; Baruönü, Fatma Özge; Kirezli, Özge; Kaytaz Yiğit, Melis; Öztunç, Müge (International Review of Management and Marketing, 2026)
Plus-size consumption is rising worldwide; retailers, marketers, and apparel manufacturers need to define consumer expectations to develop responsive strategies and tactics. This study investigates how plus-size females’ weight-based stigma coping strategies—reappraisal and disengagement—influence their apparel store choices and the moderating role of body esteem. Findings indicate that consumers adopt disengagement coping more frequently than reappraisal. Regarding channel selection, individuals who use reappraisal strategies significantly prefer online and regular stores, whereas those who adopt disengagement tend to favor plus-size stores. A key original contribution of this research is that although low body esteem increases the likelihood of disengagement at lower levels of weight-based stigma, on the other hand, under high-stigma conditions, no difference is observed in the disengagement response regardless of the female’s body esteem level.